Adjuvant DNA vaccine pNMM promotes enhanced specific immunity and anti-tumor effects - Yu Wang; Weiwei Song; Qiang Xu; Yachao Liu; Hezhong Liu; Runzi Guo; Chuang-Jiun Chiou; Kun Gao; Baofeng Jin; Changfeng Chen; Zhongming Li; Jinqi Yan; et al. (Taylor & Francis Group, 2023)
DNA vaccines containing only antigenic components have limited efficacy and may fail to induce effective immune responses. Consequently, adjuvant molecules are often added to enhance immunogenicity. In this study, we generated a tumor vaccine using a plasmid encoding NMM (NY-ESO-1/MAGE-A3/MUC1) target antigens and immune-associated molecules. The products of the vaccine were analyzed in 293 T cells by western blotting, flow cytometry, and meso-scale discovery electrochemiluminescence. To assess the immunogenicity obtained, C57BL/6 mice were immunized using the DNA vaccine. The results revealed that following immunization, this DNA vaccine induced cellular immune responses in C57BL/6 mice, as evaluated by the release of IFN-γ, and we also detected increases in the percentages of nonspecific lymphocytes, as well as those of antigen-specific T cells. Furthermore, immunization with the pNMM vaccine was found to significantly inhibit tumor growth and prolonged the survival of mice with B16-NMM+-tumors. Our data revealed that pNMM DNA vaccines not only confer enhanced immunity against tumors but also provide a potentially novel approach for vaccine design. Moreover, our findings provide a basis for further studies on vaccine pharmacodynamics and pharmacology, and lay a solid foundation for clinical application.